Effect of foam-filling on collapse mode transition of thin-walled circular columns under axial compression: Analytical, numerical and experimental studies. (January 2019) - Yang, Fan; Fan, Hualin; Meguid, S.A.
Highlights: Effect of foam filling on the concertina-to-diamond mode transition is investigated. Analytical model is established based on kinematically admissible folding mechanism. A mode classification chart is established on the R / t – σ foam / σ yt plane. The analytical model is validated by experiments and FE simulations. Abstract: Existing experimental and numerical simulations using the finite element method confirm that the collapse mode of thin-walled columns transforms from diamond to concertina as a result of foam filling. To the authors' knowledge, no attempt has been made to explain this transition analytically. This paper presents a first effort to analytically establish the effect of foam-filling and column geometry on the transition of the collapse mode. In this study, the foam/column shell interaction is represented as a uniform pressure equalling to the foam plateau stress applied on the interior of the fold walls. The predictions of the newly developed analytical model are compared with FE simulations and experimental findings and reveal good agreement. A mode classification design chart is developed to show the dependence of collapse mode on the ratio of column diameter to thickness and the ratio of filler plateau stress to column yield stress. It indicates that the column will collapse in a diamond mode when the radius-to-thickness ratio is large (>25) and the foam plateau stress/column yield stress is small (<0.015); otherwise it will collapse in a concertina mode.